Pengaruh Pemberian Air Kelapa Muda (Cocos nucifera L.) dan Jenis Varietas Terhadap Viabilitas dan Vigor Benih Kacang Panjang (Vigna sinensis L.) - Aslina Silaban; Darso Sugiono; H.M. Yamin Samaullah (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research was conducted from September to October 2020 at the Agronomy Laboratory of the Faculty of Agriculture, Singaperbangsa Karawang University, Jl. H.S Ronggowaluyo (0267) 641177 Ex. 311 Teluk Jambe Timur, West Karawang. Factorial Completely Randomized Design (CRD). The first factor is the concentration of Young Coconut Water: (K0 = 0%) (K1 = 25%) (K2 = 50%) (K3 = 75%) and the second factor is Variety Diversity: V1 New Jaliteng Variety, V2 Local Kuningan, V3 Local Bekasi and V4 Local Karawang each - each treatment was repeated 2 times so that there were 32 experimental units. The effect of the experiment was tested by analysis of variance and if the F test at 5% level showed significant results, then to determine the best treatment, further DMRT level 5% was carried out. The results showed that there was a significant effect between the provision of young coconut water and the variety of varieties on the observed variables of Vigor Index and Germination. Growth Potential, Simultaneous Growth and Growth Speed. The best treatment at the concentration of Young Coconut Water is 75% and the variety is New Jeliteng.